An Analysis Of Sensor Placement For Vehicle’s Blind Spot Detection And Warning System - Jamaluddin, Muhammad Herman; Shukor, Ahmad Zaki; Miskon, Muhammad Fahmi; Ali @ Ibrahim, Fariz; Redzuan, Muhammad Qamarul Arifin (Penerbit UTeM, 2016)
-